Painful skin lesions and squamous cell carcinoma predict overall mortality risk in organ transplant recipients: a cohort study. (1st May 2017) - Oh, C.C.; Hofbauer, G.F.L.; Serra, A.L.; Harwood, C.A.; Mitchell, L.; Proby, C.M.; Olasz, E.B.; Mosel, D.D.; Piaserico, S.; Fortina, A.B.; Geusau, A.; Jahn‐Bassler, K.; et al.
Summary: Background: Organ transplant recipients (OTRs) have a highly increased risk of cutaneous squamous cell carcinomas (SCCs). Sensation of pain in cutaneous tumours is a powerful patient‐reported warning signal for invasive SCCs in OTRs. Objectives: To investigate the impact of painful vs. painless skin lesions and SCC vs. other skin lesions on the overall mortality risk in OTRs. Methods: We followed 410 OTRs from 10 different centres across Europe and North America between 2008 and 2015. These patients had been enrolled in an earlier study to define clinically meaningful patient‐reported warning signals predicting the presence of SCC, and had been included if they had a lesion requiring histological diagnosis. Cumulative incidences of overall mortality were calculated using Kaplan–Meier survival analysis, and risk factors were analysed with Cox proportional hazard analysis. Results: There was an increased overall mortality risk in OTRs who reported painful vs. painless skin lesions, with a hazard ratio (HR) of 1·6 [95% confidence interval (CI) 0·97–2·7], adjusted for age, sex and other relevant factors. There was also an increased overall mortality risk in OTRs diagnosed with SCC compared with other skin lesions, with an adjusted HR of 1·7 (95% CI 1·0–2·8). Mortality due to internal malignancies and systemic infections appeared to prevail in OTRs with SCC. Conclusions: We suggest that OTRs have an increased overall mortality risk if they develop painful skin lesions or are diagnosed with cutaneous SCC.